The Impact of Menstrual Cycle Phases on Athletic Performance: A Comprehensive Review - Rosińska-Lewandoska, Dominika; Lewandowska, Dominika; Ufnal, Julia; Podraza, Anna; Strep, Dominika; Grabowska, Julia; Kwiatkowski, Maciej; Romańczyk, Patryk; Białczak, Julia; Kanownik, Weronika (Journal of Education, Health and Sport, 2025)
Introduction The menstrual cycle influences various physiological systems, including energy metabolism, neuromuscular function, and psychological states, which collectively impact athletic performance. Despite increased research in this area, findings remain inconsistent due to individual variability and methodological differences. This review synthesizes current evidence on the effects of menstrual cycle phases on athletic performance to identify actionable strategies for female athletes. Materials and Methods A systematic review of 35 studies published between 2019 and 2025 was conducted using PubMed and PMC databases. Inclusion criteria focused on studies examining the physiological, psychological, or performance-related effects of menstrual cycle phases. Each study was evaluated for its methodology, population, and outcomes to ensure a comprehensive analysis. Analysis of the Literature This review explores the influence of hormonal fluctuations during the menstrual cycle on energy metabolism, neuromuscular function, endurance, strength, and psychological aspects. It highlights individualized recovery strategies and long-term adaptations to phase-specific training. Conclusions Menstrual cycle phases exert significant, though variable, effects on athletic performance. While the follicular phase favors carbohydrate metabolism and high-intensity activities, the luteal phase supports fatigue resistance and fat utilization. Personalized training protocols informed by hormonal profiling can optimize outcomes, though further research is needed to standardize methodologies and evaluate long-term adaptations.